Coordination Chemistry of the Chiral, Facially Coordinating Tridentate Ligand 1, 2‐Bis(benzimidazol‐2‐yl)ethanol with 3d Transition Metals. Issue 37 (28th September 2018) - Granelli, Matteo; Downward, Alan M.; Deville, Claire; Franco, Alejandro Rodriguez; Guénée, Laure; Besnard, Céline; Williams, Alan F.
Abstract : 1, 2‐Bis(benzimidazol‐2‐yl)ethanol (1 ) and its bis‐ N ‐methylated derivative (2 ) act as chiral tridentate facially coordinating ligands capable of binding metals right across the d‐series. Octahedral complexes of divalent and trivalent metal ions are synthesised and characterised by X‐ray crystallography. Only two of the three possible diastereomers are observed in complexes of the type [M(1, 2 )2 ] and appear to be close in energy. In complexes of M II ions, the alcohol function of the ligand stays protonated, but the proton is lost in complexes of M III ions. Electronic and CD spectra are reported. Slow oxidation of the vanadium(III) complex leads to a mixed valence compound where one ligand has been oxidised. Abstract : 1, 2‐Bis(benzimidazol‐2‐yl)ethanol is a versatile tridentate ligand binding facially to almost all first row transition metals in II and III oxidation states giving chiral octahedral complexes. Complexes of M III metals show deprotonation of the alcohol group. Syntheses and structures are reported and the varied stereochemistry and CD spectra are discussed.